Analisa Risiko K3 dengan Metode Job Safety Analysis (JSA) dan Risk Assessment pada Proses Mesin Sizing di PC GKBI Medari Sleman - Muh. Dawami Sholichin; Yunita Primasanti; Bekti Nugrahadi; Erna Indtriastiningsi; Anita Oktaviana Trisna (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Occupational Health and Safety (OHS) is a crucial aspect of the textile industry to ensure worker protection and maintain smooth production processes. This study aims to identify and analyze potential occupational accident risks in the sizing machine process. The methods used in this research are Job Safety Analysis (JSA) and Risk Assessment to evaluate workplace hazards that may disrupt operations. The results indicate several major risks in the sizing process, including mechanical hazards due to direct contact with machines, ergonomic hazards caused by improper working postures, and chemical hazards from exposure to cotton dust and sizing solution vapors. The main risk factors include human aspects, the work environment, and machinery. The recommended improvements in this study include enhancing work supervision and control, providing safety training for workers, optimizing workplace ergonomics, and conducting regular machine maintenance to reduce accident risks. The proper implementation of safety strategies is expected to improve production efficiency and create a safer and more conducive work environment.